2015
DOI: 10.1111/avsc.12183
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide application as a habitat restoration tool: impact on native island plant communities

Abstract: Questions Which physical or chemical removal method is most effective in controlling woody invasive alien plant (IAP) species in sensitive conservation areas, while minimizing the impact on different life stages of native plant communities? Is there a distinct influence of removal method on successional trajectories of post‐treatment seedling communities? Location Mid‐altitude inselbergs, Mahé, Seychelles, Indian Ocean. Methods We conducted two field experiments. First, to test the effects of four IAP control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…() found key native grassland forbs were rare 16 yr after picloram control for non‐native plants, and others found temporary declines in native species richness and diversity (Kaiser‐Bunbury et al. ). When certain species are eliminated they may leave niches that can be filled by other non‐native species (Pearson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() found key native grassland forbs were rare 16 yr after picloram control for non‐native plants, and others found temporary declines in native species richness and diversity (Kaiser‐Bunbury et al. ). When certain species are eliminated they may leave niches that can be filled by other non‐native species (Pearson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, native forbs did not establish on heavily invaded sites and declined as non-native forbs increased at a less invaded site. Rinella et al (2001) found key native grassland forbs were rare 16 yr after picloram control for non-native plants, and others found temporary declines in native species richness and diversity (Kaiser-Bunbury et al 2015). When certain species are eliminated they may leave niches that can be filled by other non-native species (Pearson et al 2016).…”
Section: Non-native Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Between 2011 and 2012, four of the inselbergs were cleared of all non-native plants with the aim to restore native plant communities, while the other four were left with both native and non-native species (Kaiser-Bunbury et al 2015). Irregular maintenance of the "restored" sites resulted in encroachment of previously removed and recently arrived non-native plant species, mainly C. hirta and C. verum (A. Costa personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…1 ha each on Mahé, the largest granitic island of the Seychelles, Indian Ocean (-4.6953 • , 55.4999 • , 154 km 2 , 900 m a.s.l.). Between 2011 and 2012, all non-native plants were removed from four of the inselbergs to restore plant communities, while the other four sites remained unaltered with both native and non-native species (Kaiser-Bunbury et al, 2015). Hereafter, we refer to sites undergoing restoration as "restored" and sites invaded by non-native plant species as "unrestored".…”
Section: Study Systemmentioning
confidence: 99%